Napoli Città-Paese. Un libero peregrinare tra "storia" e "storie" - Coletta, Mario (TRIA Urban Studies, 2022)
The essay aims to propose a double way of reading the urban context of Naples, addressing in the first part a chronological review of the events that accompanied its urban growth, from its foundation to the present, in order to synthesize the evolutionary characteristics that defined Naples as a "City ", in relationship with the political and administrative events that determined them and the social, economic and cultural repercussions that ensued. In the second part, the point of observation has been changed. Starting from the peculiarities of the Neapolitan "vicolo" (alley), considered as a "Paese" (Town), a fundamental element for urban life and vitality, the author studies its socio-behavioural, settlement, economic and cultural characteristics, considering the narrative testimony, the artistic representation and the cultural manifestations that have animated and still animate the transmission of memories. The research starts from the consideration that in the Neapolitan "vicolo", as in the whole city, even the foreigner is, after World War II, called "Paisano" (villager) as well as in post-revolutionary France every person was considered as a "Cittadino" (citizen).